Characterization of type I L-asparaginase encoding gene from the thermohalophilic bacterium Bacillus subtilis CAT3.4 from Wawolesea Hot Spring, Southeast Sulawesi, Indonesia - MUZUNI MUZUNI; MUHAMAD ILHAM; ARDIANSYAH ARDIANSYAH; SURIANA SURIANA; YUTRIANA PUTRI; KARTINA KARTINA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Muzuni, Ilham M, Ardiansyah, Suriana, Putri Y, Kartina. 2023. Characterization of type I L-asparaginase encoding gene from the thermohalophilic bacterium Bacillus subtilis CAT3.4 from Wawolesea Hot Spring, Southeast Sulawesi, Indonesia. Biodiversitas 24: 5167-5178. This study aims to determine the molecular characteristics of the gene encoding type 1 L-asparaginase from CAT3.4 thermohalophilic bacterial isolates from the hot springs of Wawolesea, North Konawe, Southeast Sulawesi. This enzyme can be used as a cancer therapy agent and prevents the formation of acrylamide in food products. It is a kind of exploratory research. The characterization was done by amplifying the ansA gene sequence encoding L-asparaginase from CAT3.4 isolate by polymerase chain reactions (PCR) technique using primers AsnBac1-F1 (5'-ACGCGATATTTCTTTTGGCCGG-3') and AsnBac1-R1 (5'-CAGTGAAGAGGTGCATGGTATG-3'). The amplified PCR product was used as a template for sequencing by the Sanger method. The amino acid coding regions (CDS) obtained were bioinformatically characterized using the NCBI website for BLASTn analysis, restriction site and hydrophobicity profiles were analyzed using the BioEdit program, phylogenetic tree was analyzed using the MEGA X program, and type 1 L-asparaginase amino acid sequence was analyzed using the Expasy translate program. The characterization results showed that the target gene has a high similarity to the ansA gene sequence of 20 Bacillus subtilis strains, i.e., 99-100%, is closely related to the ansA gene of Bacillus subtilis strain SRCM103629 and Bacillus subtilis strain GOT9, can be identified using restriction enzymes MluI and BstI to differentiate the species of organisms they produce, has CDS encoding 329 amino acids with a dominant composition of polar amino acids (54.1%) and has a hydrophobicity profile of amino acids dominated by hydrophilic regions. All these characteristics have confirmed that the characterized gene is the ansA gene encoding type 1 L-asparaginase from Bacillus subtilis. The finding of the ansA gene from Bacillus subtilis in a thermohalophilic region in Southeast Sulawesi, Indonesia is a novelty of the research.